Relationship Between Buddhist Belief and Suicide Risk in Chinese Persons Undergoing Methadone Maintenance Therapy for Heroin Dependence - Huang, Jian-Xing; Xu, Yan-Min; Zhong, Bao-Liang (Frontiers in Psychiatry, 2020)
Background: In western countries, there is a negative association between religious belief and suicide risk, while in China this association is positive. Nevertheless, few data are available on the association between one specific type of religion and suicide risk, which might be different from the overall positive religion-suicide association in China. This study examined the association between Buddhist belief and suicide risk in Chinese persons receiving methadone maintenance therapy (MMT) for heroin dependence. Methods: In total, 61 Buddhist believers and 425 age, gender, and clinic frequency-matched non-religious believers were selected from a sample of patients with heroin dependence treated in three MMT clinics in Wuhan, China. The suicidality module of the Chinese version of the Mini-international Neuropsychiatric Interview 5.0 was used to assess current suicide risk. Patients’ demographic and clinical characteristics were also collected. Multiple ordinary logistic regression was used to analyze the association between Buddhist belief and current suicide risk, controlling for the confounding effects of demographic and clinical factors. Results: In Chinese patients receiving MMT for heroin dependence, Buddhist believers had significantly higher levels of current suicide risk than non-religious believers (low: 45.9% vs. 24.7%, medium: 4.9% vs. 3.5%, high: 19.7% vs. 12.5%, P<0.001). After adjusting for demographic and clinical covariates (including depressive symptoms), Buddhist belief was still significantly associated with an increase in the level of current suicide risk (OR: 2.98, P<0.001). Conclusion: Buddhist belief is significantly associated with elevated current suicide risk in Chinese patients receiving MMT for heroin independence. In Chinese MMT clinics, patients with Buddhist belief may have a high current suicide risk and a timely psychiatric assessment and crisis intervention (when necessary) should be provided to these patients.